Cytosolic and Nucleosolic Calcium Signaling in Response to Osmotic and Salt Stresses Are Independent of Each Other in Roots of Arabidopsis Seedlings - Huang, Feifei; Luo, Jin; Ning, Tingting; Cao, Wenhan; Jin, Xi; Zhao, Heping; Wang, Yingdian; Han, Shengcheng (Frontiers in Plant Science, 2017)
Calcium acts as a universal second messenger in both developmental processes and responses to environmental stresses. Previous research has shown that a number of stimuli can induce [Ca2+] increases in both the cytoplasm and nucleus in plants. However, the relationship between cytosolic and nucleosolic calcium signaling remains obscure. Here, we generated transgenic plants containing a fusion protein, comprising rat parvalbumin (PV) with either a nuclear export sequence (PV-NES) or a nuclear localization sequence (NLS-PV), to selectively buffer the cytosolic or nucleosolic calcium. Firstly, we found that the osmotic stress-induced cytosolic [Ca2+] increase (OICIcyt) and the salt stress-induced cytosolic [Ca2+] increase (SICIcyt) were impaired in the PV-NES lines compared with the Arabidopsis wildtype (WT). Similarly, the osmotic stress-induced nucleosolic [Ca2+] increase (OICInuc) and salt stress-induced nucleosolic [Ca2+] increase (SICInuc) were also disrupted in the NLS-PV lines. These results indicate that PV can effectively buffer the increase of [Ca2+] in response to various stimuli in Arabidopsis. However, the OICIcyt and SICIcyt in the NLS-PV plants were similar to those in the WT, and the OICInuc and SICInuc in the PV-NES plants were also same as those in the WT, suggesting that the cytosolic and nucleosolic calcium dynamics are mutually independent. Furthermore, we found that osmotic stress- and salt stress-inhibited root growth was reduced dramatically in the PV-NES and NLS-PV lines, while the osmotic stress-induced increase of the lateral root primordia was higher in the PV-NES plants than either the WT or NLS-PV plants. In addition, several stress-responsive genes, namely CML37, DREB2A, MYB2, RD29A, and RD29B, displayed diverse expression patterns in response to osmotic and salt stress in the PV-NES and NLS-PV lines when compared with the WT. Together, these results imply that the cytosolic and nucleosolic calcium signaling coexist to play the pivotol roles in the growth and development of plants and their responses to environment stresses.